(untitled) (Swiss Medical Weekly, 2016)
Dual-energy computed tomography (DECT) angiography of the chest provides a combined morphological and functional analysis of the lung, usually obtained in a single acquisition without extra radiation or injection of extra intravenous iodine contrast. The parenchymal iodine maps generated by DECT are well correlated with scintigraphy, and are becoming an essential tool for evaluating patients with pulmonary vascular diseases. With a single DECT acquisition, complete imaging of pulmonary hypertension is now available, displaying vascular anatomy, parenchymal morphology and functional assessment. Triangular pulmonary perfusion defects in chronic thromboembolic pulmonary hypertension may be clearly analysed even in the presence of distal arterial occlusion. Perfusion heterogeneities seen in patients with pulmonary arterial hypertension reflect mosaic perfusion and may be helpful for the diagnosis, severity assessment and prognosis of the disease. Vascular or parenchymal abnormalities can also be analysed with perfusion defects to determine their aetiology. Pulmonary arterial hypertension due to congenital heart disease can be assessed with a single DECT, even in the neonatal population. Furthermore, new applications are emerging with ventilation imaging or myocardial perfusion imaging obtained by DECT and should be considered. In conclusion, DECT of the thorax enables the simultaneous and noninvasive assessment of vascular anatomy, parenchymal morphology and functional pulmonary imaging in various groups of PH.